Evaluation of thermal and photovoltaic solar systems in agricultural production units, Northern Huetar Region, Costa Rica - Guzmán Hernández, Tomás de Jesús; Araya Rodríguez, Freddy; Obando Ulloa, Javier Mauricio; Rivero Marcos, Mikel; Castro Badilla, Guillermo (Agronomía Mesoamericana, 2017)
The dependence on fossil fuels urges society to seek for clean energy alternatives, in order to mitigate the effects of climate change. The objective of this study was to determine the potential of solar energy used for water heating and electricity generation. The study was conducted at the dairy of the Technology Institute of Costa Rica, San Carlos Headquarter, from May 15 to April 2016. The data related to the amount of the electricity produced and the temperature reached by water was obtained from the installed photovoltaic and thermal systems, the data was recorded by a computerized register. The obtained information about electricity production allowed researchers to calculate the amount of carbon dioxide equivalent that was not emitted into the atmosphere, and also the acquired economic saving on consumption. The use of these systems allowed the production unit have a self- sufficient source of electrical energy percentage, actually around 30 to 40% of the total electrical consumption. According to the energy production, the solar thermal system was capable to increase water temperature between 20 to 37 °C, temperature that represents more than 70% of the energy needed in order to reach the required water temperature (70 °C) for cleaning and sanitizing the milking equipment, and also an economical saving around $90 per month was achieved. The results showed that these systems allow to improve the economical and productive efficiency of agricultural production units in the Northern Huetar Region of Costa Rica.